Pleasure and Suffering at Work in a Private Higher Education Institution in Minas Gerais - Vieira Martins, Andrea Arnaut; Honório, Luiz Carlos (Organizações & Sociedade, 2014)
This study examines the perception of teachers from a higher education private institution in Belo Horizonte on the experience of pleasure and suffering at work, using a quantitative and qualitative case study. The quantitative data obtained indicated that most of the results ranged from critical to serious. The professional accomplishment was the most relevant pleasure in the work, while burnout was selected as the most critical factor of suffering at work. The study showed positive associations between: a) suffering at work (lack of recognition and burnout) with age and time in teaching, b) suffering at work (burnout) with socio-professional relations (work management, communication and professional interaction). The qualitative data revealed that precarization elements at work were considered as triggers of suffering at work, especially those related to autonomy, the assessment’s new forms in higher education and peer relationships.